2009
DOI: 10.1002/tl.341
|View full text |Cite
|
Sign up to set email alerts
|

Supportive teaching and learning strategies in STEM education

Abstract: This chapter provides faculty with design principles based on the How People Learn framework, as well as current best practices for designing engaged learning environments in STEM classes in the hope of continuing improvement in STEM education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…Numerous educational researchers have also advocated for an integrated curriculum (e.g., Bybee, 2010;Czerniak et al, 1999;Frykholm & Glasson, 2005;Kiray, 2012;Moscovici & Newton, 2006;Smith, Douglas, & Cox, 2009). Czerniak et al, (1999) found integration to be an authentic approach to education, while others found that integration improves student achievement (Beane, 1995;Vars, 1991).…”
Section: The Importance Of Integrationmentioning
confidence: 99%
“…Numerous educational researchers have also advocated for an integrated curriculum (e.g., Bybee, 2010;Czerniak et al, 1999;Frykholm & Glasson, 2005;Kiray, 2012;Moscovici & Newton, 2006;Smith, Douglas, & Cox, 2009). Czerniak et al, (1999) found integration to be an authentic approach to education, while others found that integration improves student achievement (Beane, 1995;Vars, 1991).…”
Section: The Importance Of Integrationmentioning
confidence: 99%
“…al discuss best practices for implementation of co-operative learning and problembased learning as a part of the effort to improve Science, Technology, Engineering, and Mathematics (STEM) education. 16 Deslauriers et. al present the value in learning and engagement of methods that would require the students to practice physicist-like reasoning and problem solving during class time while provided with frequent feedback.…”
Section: Research On Improving Student Learningmentioning
confidence: 99%
“…However, traditional engineering curriculum and coursework lacks important student learning opportunities, such as; the reason why these concepts or mathematics are important, what is their real-world relevance and how this will impact the students' future career in engineering. An alternative to the traditional teaching method is inductive learning, which is a student-centered approach that encompasses many pedagogical methods including; Active and Collaborative Learning (ACL), Problem Based Learning (PBL) and others (Smith et al, 2005;Smith et al, 2009). These techniques begin with a real world problem or observation that is introduced to the students.…”
Section: Motivation To Include "Entrepreneurial Minded Learning" In Tmentioning
confidence: 99%